The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1558-5646.2011.01273.x
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding and Reproductive Investment in the Ant Formica Exsecta

Abstract: In social animals, inbreeding depression may manifest by compromising care or resources individuals receive from inbred group members. We studied the effects of worker inbreeding on colony productivity and investment in the ant Formica exsecta. The production of biomass decreased with increasing inbreeding, as did biomass produced per worker. Inbred colonies produced fewer gynes (unmated reproductive females), whereas the numbers of males remained unchanged. As a result, sex ratios showed increased male bias, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 116 publications
1
39
1
Order By: Relevance
“…Another possibility is that nurse workers can assess the number of queens directly or by colony egg production, and use this as a proxy to adjust sex ratio in polygynous colonies. This is consistent with split-sex ratio theory (Boomsma, 1993), because polygynous colonies will tend to have higher eggproduction and a lower than population-level-average relatedness asymmetry, and also with the idea that specialization in the cheaper sex (males weigh less in F. exsecta; Vitikainen et al, 2011) requires greater initial eggproduction for equal total biomass production. On the other hand, this does not explain the tendency of monogynous/ polyandrous colonies to specialize in male production.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Another possibility is that nurse workers can assess the number of queens directly or by colony egg production, and use this as a proxy to adjust sex ratio in polygynous colonies. This is consistent with split-sex ratio theory (Boomsma, 1993), because polygynous colonies will tend to have higher eggproduction and a lower than population-level-average relatedness asymmetry, and also with the idea that specialization in the cheaper sex (males weigh less in F. exsecta; Vitikainen et al, 2011) requires greater initial eggproduction for equal total biomass production. On the other hand, this does not explain the tendency of monogynous/ polyandrous colonies to specialize in male production.…”
Section: Discussionsupporting
confidence: 79%
“…Fletcher and Michener, 1987), but this lack of relationship may be explained by the uniform levels of genetic variation we found among the different colony types. The breeding patterns and the genetic structure of the population, which indicate non-trivial levels of inbreeding Haag-Liautard et al, 2009;Vitikainen et al, 2011), may have contributed to the depauperate chemical profile through genetic purging, a question which will have to be addressed in future studies. We also found that the within-colony CHC variability does not allow accurate assessment of colony kin structure, and that workers do not seem to use any single compound or set of compound as a proxy for sex ratio adjustments.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations